Repetitive DNA in the Architecture, Repatterning, and Diversification of the Genome of Aegilops speltoides Tausch (Poaceae, Triticeae) - Pollak, Yulia; Zelinger, Einat; Raskina, Olga (Frontiers in Plant Science, 2018)
Abstract The genome’s adaptability to environmental changes, especially during rapid climatic fluctuations, underlies the existence and evolution of species. In the wild, genetic and epigenetic genomic changes are accompanied by significant alterations in the complex nuclear repetitive DNA fraction. Current intraspecific polymorphism of repetitive DNA is closely related to ongoing chromosomal rearrangements, which typically result from erroneous DNA repair and recombination. In this study, we addressed tandem repeat patterns and interaction/reshuffling both in pollen mother cell (PMC) development and somatogenesis in the wild diploid cereal Aegilops speltoides, with a focus on genome repatterning and stabilization. Individual contrasting genotypes were investigated using the fluorescent in situ hybridization (FISH) approach by applying correlative fluorescence and electron microscopy. We found that, in the interphase nuclei, different types of tandem repeat sequences aggregate in complex clusters. The frequencies of nonhomologous/ectopic associations between tandem repeat clusters were revealed in a genotype-/population-specific manner. The distal/terminal regions of homologous chromosomes are separated in nuclear space, and nonhomologous chromosomes are frequently involved in somatic recombination. In both microgametogenesis and somatogenesis, inter- and intrachromosomal associations lead to DNA breaks during chromosome disjunction in the anaphase stage. As a result of broken associations, uncondensed/improperly packed DNA fibers, mainly in heterochromatic regions, were revealed in both the meiotic and somatic prophases. It was proposed that cell-specific ectopic recombination events that occurred in premeiotic cell lineages result significant numbers of nonhomologous chromosomal associations detected in microgametogenesis. Especially in heterochromatin, DNA regions that remain unrepaired and uncondensed provoke chromosome aberrations in the following cell cycle. However, chromosomal rearrangements cause heterochromatic cluster repatterning, which is required for genome homogenization/stabilization under the conditions of natural out-crossing and intraspecific hybridization in Ae. speltoides. Altogether, the data obtained showed that perpetual intraorganismal reshuffling of repetitive DNA mirrors the structural plasticity of the Ae. speltoides genome, which is interlinked with genetic diversity through the species distribution area in contrasting ecogeographical environments in and around the Fertile Crescent.